Expression of Rho Guanine Nucleotide Exchange Factor 39 (ARHGEF39) and Its Prognostic Significance in Hepatocellular Carcinoma - Gao, Jian (Med Sci Monit, 2019)
BACKGROUND: Previous studies have reported that ARHGEF39 might be frequently upregulated in different cancer types and relevant to cancer progression. However, the expression pattern and clinicopathological features of ARHGEF39 in patients with hepatocellular carcinoma (HCC) needs further exploration. MATERIAL/METHODS: ARHGEF39 expression level of HCC in The Cancer Genome Atlas (TCGA) dataset was analyzed. Quantitative real-time polymerase chain reaction and immunohistochemistry were employed to determine ARHGEF39 mRNA and protein levels in our own study collected HCC tissues and matched non-cancerous tissues. Moreover, the association of ARHGEF39 expression with the clinicopathological factors and prognosis of HCC were investigated. RESULTS: The level of ARHGEF39 in HCC tissues was significantly higher than that in adjacent normal tissues (P<0.05) from TCGA database. High level of ARHGEF39 was a significant prognostic factor of poor overall survival (OS) (TCGA, P=0.006). Consistently, the expression levels of ARHGEF39 mRNA and protein in HCC specimens were significantly higher than those in adjacent liver specimens (P<0.05) from our cohort. Further analysis revealed that high ARHGEF39 level was significantly associated with poor OS (P<0.001) and short disease-free survival (DFS) (P<0.001). Cox multivariate analysis indicated that ARHGEF39 was an independent, unfavorable prognostic factor (P=0.000) of OS and DFS. CONCLUSIONS: ARHGEF39 might act as an oncogene in the progression of HCC and might serve as a promising potential prognostic indicator and therapeutic target for HCC.